Design, synthesis and biological evaluation of 2-(3, 4-dimethoxyphenyl)-6 (1, 2, 3, 6-tetrahydropyridin-4-yl)imidazo[1, 2-a]pyridine analogues as antiproliferative agents. Issue 18 (15th September 2019) - Chitti, Surendar; Singireddi, SrinivasaRao; Santosh Kumar Reddy, Pochana; Trivedi, Prakruti; Bobde, Yamini; Kumar, Chandan; Rangan, Krishnan; Ghosh, Balaram; Sekhar, Kondapalli Venkata Gowri Chandra
Graphical abstract: Highlights: Designed, synthesized and evaluated 45 novel Imidazo [1, 2- a ] pyridine derivatives. Derivatives show potent anticancer activity in HeLa, A549 and B16F10 cell lines with IC50 2.0–20.0 µM. IPA-5 and IPS-7 induced significant apoptosis in B16F10 cells. IPA 5, 6, 8, 9, 12, 16, 17, 19 and IPS 7, 8, 9, 22 were not toxic in HEK cell line in the tested IC50 range. Abstract: Two series of forty five novel 2-(3, 4-dimethoxyphenyl)-6-(1, 2, 3, 6-tetrahydropyridin-4-yl) imidazo[1, 2- a ]pyridine analogues (IPA 1 –22, IPS 1 –22 and IP-NH ) have been designed, synthesized and structures confirmed by 1 H NMR, 13 C NMR, mass spectrometry. Furthermore, single crystal was developed for IPS-13 . All the final derived conjugates were evaluated for their in vitro antiproliferative activity against a panel of diverse cancer cell lines viz., A549 (lung cancer), HeLa (cervical cancer), B16F10 (melanoma) and found to show potent anticancer activity on the tested cell lines. Many of them showed the IC50 values in the range 2.0–20.0 µM. The most active compounds (IPA 5, 6, 8, 9, 12, 16, 17, 19 and IPS 7, 8, 9, 22 ) from IPA and IPS series were screened to determine their cytotoxicity on HEK-293 (human embryonic kidney) normal cell line and were found to be nontoxic to normal human cells. The molecular interactions of the derivatised conjugates were also supported by molecular docking simulations. These derivatives may serve as lead structures for development of novel potential anticancer drug candidates.